Kerr-lens mode locking in a ring bidirectional YAG:Cr4+ laser - Broslavets, Yu.Yu.; Georgieva, M.A.; Fomitchev, A.A. (ALT Proceedings, 2026)
This paper concerns a bidirectional ring YAG:Cr4+lаser. We investigated the features of bidirectional generation and explored the possibility of gyroscopic effect in the laser. We developed the model of bidirectional generation of such a laser taking into account spectral properties of the active medium.Experiments in our setup revealed that generation of the laser had a cluster character. Luminescence spectrum of the YAG:Cr4+ crystal and generation spectra of the laser showed that this medium has both homogeneous and inhomogeneous broadenings. Stable bidirectional generation is a result of the fact that competition between counterpropagating waves is less than in the case of homogeneously broadened medium.